Potential use of Several Fungalendofit Fungus in Rubber Crops (Hevea Brasiliensis) Plant for Healrth Invesment (Colletotrichum gloeosporiodes) in Rubber Plant - Ginting, Sulaiman (PT Inovasi Pratama Internasional, 2024)
Rubber is a key plantation commodity in Indonesia, serving as a significant source of non-oil and gas foreign exchange. However, rubber productivity remains low, largely due to inadequate cultivation technology and the impact of pests and diseases. One of the most economically significant diseases affecting rubber plants is deciduous disease caused by Colletotrichum gloeosporioides, which spreads through spores carried by wind and rain. This study was conducted at the Sungei Putih Rubber Research Institute, North Sumatra, from February to June 2019, at an elevation of ± 25 meters above sea level. A factorial randomized block design (RBD) with three replications was employed. The treatments included three types of endophytic fungi (E1, E2, E3) derived from different isolates of PB 260 rubber clones, and four application methods (M0, M1, M2, M3). The observed parameters included latent period, disease occurrence, and disease intensity. The results indicated that the E2M2 treatment, which combined the second endophytic fungus with metabolite application, was the most effective in controlling C. gloeosporioides deciduous disease. This combination resulted in the highest average latent period (3.67%), the lowest disease occurrence (0.03%), and the most effective reduction in disease intensity (17.67% after 12 days). The study demonstrates the potential of specific endophytic fungi and application methods in managing rubber plant diseases, offering insights for improving rubber productivity in Indonesia.